Phase 1, open-label, dose-escalation, and pharmacokinetic study of STAT3 inhibitor OPB-31121 in subjects with advanced solid tumors - Bendell, Johanna C.; Hong, David S.; Burris, Howard A.; Naing, Aung; Jones, Suzanne F.; Falchook, Gerald; Bricmont, Patricia; Elekes, Agnes; Rock, Edwin P.; Kurzrock, Razelle (Cancer chemotherapy and pharmacology, 2014)
Purpose To determine the maximum tolerated dose (MTD) and biologic activity of OPB-31121, an oral inhibitor of STAT3, administered twice daily (BID) to subjects with advanced solid tumors. Methods .Subjects received escalating doses of OPB-31121 BID for the first 21 days of each 28-day cycle in a standard 3 + 3 design. Dose-limiting toxicities (DLTs), safety, pharmacokinetics, and antitumor activity were assessed. Results Thirty subjects were treated twice daily with OPB-31121 at 6 dose levels: 50 mg ( n = 4); 70 mg ( n = 3); 140 mg ( n = 3); 200 mg ( n = 4); 300 mg ( n = 9); 350 mg ( n = 7). There were no DLTs observed until 300 mg BID (Grade 3 lactic acidosis). At the next dose level (350 mg BID), two subjects had DLTs (Grade 3 vomiting and Grade 3 diarrhea). Thus, 300 mg BID was declared the MTD. OPB-31121-related adverse events included nausea (80 %), vomiting (73 %), diarrhea (63 %), and fatigue (33 %), all of which were primarily grade 1/2. Pharmacokinetics demonstrated high inter-subject variability with exposures 146- to 4,788-fold lower than target concentrations from tumor-bearing mouse models. No objective responses were observed, and all subjects who completed two cycles of treatment had disease progression at their first assessment. Conclusions Twice-daily administration of OPB-31121 was feasible up to doses of 300 mg. The pharmacokinetic profile was unfavorable, and no objective responses were observed.